Hospitalization flow in the public and private systems in the state of Sao Paulo, Brazil - Juan Stuardo Yazlle Rocha; Rosane Aparecida Monteiro; Marizélia Leão Moreira (Universidade de São Paulo, 2015)
OBJECTIVE To describe the migration flows of demand for public and private hospital care among the health regions of the state of Sao Paulo, Brazil.METHODS Study based on a database of hospitalizations in the public and private systems of the state of Sao Paulo, Southeastern Brazil, in 2006. We analyzed data from 17 health regions of the state, considering people hospitalized in their own health region and those who migrated outwards (emigration) or came from other regions (immigration). The index of migration effectiveness of patients from both systems was estimated. The coverage (hospitalization coefficient) was analyzed in relation to the number of inpatient beds per population and the indexes of migration effectiveness.RESULTS The index of migration effectiveness applied to the hospital care demand flow allowed characterizing health regions with flow balance, with high emigration of public and private patients, and with high attraction of public and private patients.CONCLUSIONS There are differences in hospital care access and opportunities among health regions in the state of Sao Paulo, Brazil.